2D MoS2 Neuromorphic Devices for Brain‐Like Computational Systems. Issue 29 (31st May 2017) - Jiang, Jie; Guo, Junjie; Wan, Xiang; Yang, Yi; Xie, Haipeng; Niu, Dongmei; Yang, Junliang; He, Jun; Gao, Yongli; Wan, Qing
Abstract : Hardware implementation of artificial synapses/neurons with 2D solid‐state devices is of great significance for nanoscale brain‐like computational systems. Here, 2D MoS2 synaptic/neuronal transistors are fabricated by using poly(vinyl alcohol) as the laterally coupled, proton‐conducting electrolytes. Fundamental synaptic functions, such as an excitatory postsynaptic current, paired‐pulse facilitation, and a dynamic filter for information transmission of biological synapse, are successfully emulated. Most importantly, with multiple input gates and one modulatory gate, spiking‐dependent logic operation/modulation, multiplicative neural coding, and neuronal gain modulation are also experimentally demonstrated. The results indicate that the intriguing 2D MoS2 transistors are also very promising for the next‐generation of nanoscale neuromorphic device applications. Abstract : 2D MoS2 synaptic/neuronal transistors are fabricated using poly(vinyl alcohol) as laterally coupled, proton‐conducting electrolytes. Fundamental synaptic functions, such as an excitatory postsynaptic current, paired‐pulse facilitation, and a dynamic filter for information transmission of biological synapses, are successfully emulated. Moreover, spiking‐dependent logic operation/modulation, multiplicative neural coding, and neuronal gain modulation are also demonstrated in such MoS2 neuromorphic devices.